Regional disparities in the European Union: Convergence and Agglomeration - Kurt Geppert; Michael Happich; Andreas Stephan (European Regional Science Association (ERSA), 2004)
Economic disparities between the regions of the European Union are of constant concern both for policy and economic research. One of the “stylised facts” from the empirical literature is that the process of absolute convergence observed for decades has slowed down or even petered out during the 1980s. In this paper we analyse whether it has resumed and persisted in the 1990s when European integration made huge steps forward. We construct a typology of regions in order to examine whether there are overlapping trends of regional development, in particular, overall convergence on the one hand and persistent or even increasing spatial concentration (agglomeration) on the other. Both of our approaches, Marcov chain analysis and dynamic panel estimation, provide evidence that regional convergence in the EU15 has become stronger in the 1990s. At the same time there appears to exist a tendency towards further agglomeration of high income economic activities. Keywords: Regional growth, agglomeration, dynamic panel estimation
Keywords: 330; Regional growth; agglomeration; dynamic panel estimation